An Analysis of Cognitive Levels in Sociology Assessment Instruments for Senior High School: A Teacher Document Study - Agustina, Dwi; Martiana, Aris; Sari, Novita (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2026)
Studies that specifically analyze the distribution of cognitive levels in sociology assessment instruments remain limited. This highlights the importance of research that maps the alignment of assessment instruments developed by teachers with the competency standards outlined in the curriculum. Therefore, this study aims to map the distribution of cognitive levels in senior high school sociology assessment instruments, identify emerging content trends, and analyze the relationships among the cognitive levels represented. The study employed a qualitative method with a content analysis approach. Data were collected through document analysis of 11 assessment instruments developed by 11 senior high school sociology teachers in Sleman Regency, which included both objective and essay items. The analysis process was supported by ATLAS.ti software, and the results were presented in the form of distribution tables, Sankey diagrams, and network views. The findings indicate that the test items were dominated by the C4 (analysis) level, with 99 items, suggesting a shift in assessment focus from lower-order thinking skills (LOTS) to higher-order thinking skills (HOTS), although items at the C5 level were still limited, and the C6 level had not yet been accommodated. The content trends were dominated by contextual themes such as social problems, social structure, social interaction, and social integration, which are consistent with the intended learning competencies of sociology. The analysis of inter-level cognitive relationships revealed a supportive hierarchy: C1 to C2 (is a part of), C2 to C3 (is cause of), C3 to C4 (is cause of), C4 to C5 (is associated with), and C5 to C6 (is associated with). The implications of this study can be used to develop assessment items that promote higher-order thinking skills.